Absolute radiometric calibration of a VUV spectrometer in the wavelength range 46–300 nm. (January 2021) - Fröhler-Bachus, C.; Friedl, R.; Briefi, S.; Fantz, U.
Highlights: Vacuum ultraviolet (VUV) spectroscopy of resonant transitions in plasmas. Inhouse calibration of a VUV monochromator in the wavelength range 46–300 nm. Combination of relative standards and an absolute optical emission spectrometer. Validation via population densities of hydrogen atoms using Lyman and Balmer series. Relevance of opacity. Abstract: Vacuum ultraviolet (VUV) radiation corresponds to photon energies exceeding 6.2 eV and provides access to atomic and molecular resonant transitions in various plasmas. Determining population densities of electronic levels directly connected to the ground state requires an absolute intensity calibration of the VUV spectrometer. For this purpose, synchrotron radiation from electron storage rings is the typical primary standard source associated with transport effort and operating costs. Alternatively, a complex procedure using several secondary standards and discharges directly at the setup in use can be applied. In this work, an absolute intensity calibration avoiding synchrotron radiation to cover the wavelength range 46–300 nm accessible with two detectors—a photomultiplier tube and a channel electron multiplier—is presented. A combination of different standard sources—two deuterium arc lamps, branching-ratios of a nitrogen plasma and a high current hollow cathode—is applied for the relative calibration. The absolute calibration is based on simultaneous measurements of atomic lines in a low pressure helium discharge with the VUV spectrometer and an absolutely calibrated optical emission spectrometer. Special focus is laid on the uncertainties of the relative and absolute calibration depending on the wavelength range. The applicability of the intensity calibration is demonstrated at a hydrogen plasma in the wavelength range 80–300 nm. Using the emissivity of the Lyman series, population densities of the first six excited atomic states are calculated considering opacity effects. The excellent agreement with results from the Balmer series by optical emission spectroscopy manifests the high validity of the performed absolute intensity calibration.